Design and Comparison of Printed Antennas using Meander Line Technique - Mokhtar, Nur Hamizah Muhamad; Malek, Norun Abdul; Jusoh, Ahmad Zamani; Ali, Khamis; Isa, Farah Nadia Mohd; Rahman, Farah Diyana Abdul (Institute of Advanced Engineering and Science, 2019)
The interest for compact antennas in wireless communication increase due to the portability and mobility of the communication devices. Generally, an antenna at low frequency exhibits in large physical size. This project investigates the design of an antenna at 400 MHz. The simulation of the antenna has been performed using CST MWS. Since medical applications are dealing with low frequency, it will lead to large size of antenna which brings a challenge for wireless personal area network (WPAN). It is well known that the antenna performance decreases (according to Chu’s equation) as the size of antenna decreases. Therefore, antenna miniaturization using Meander Line (ML) will be taking place to overcome the challenges. Thus, this paper presents a comparison between i) printed dipole antenna without meander line technique, ii) printed dipole with meander line technique and iii) printed monopole antenna with meander line technique. The results show that an estimation of reduction size by 50% can be achieved using Meander Line technique.